Prospective evaluation of Globus pallidus internus deep brain stimulation in Huntington's disease. (June 2018) - Zittel, S.; Tadic, V.; Moll, C.K.E.; Bäumer, T.; Fellbrich, A.; Gulberti, A.; Rasche, D.; Brüggemann, N.; Tronnier, V.; Münchau, A.
Abstract: Introduction: Pharmacological treatment of chorea in Huntington's disease (HD) is often limited by poor efficacy or side effects. Pallidal deep brain stimulation (DBS) has been considered in these patients but experience is so far limited. Methods: We prospectively evaluated the effects of bilateral DBS of the Globus pallidus internus (GPi) over one year in six severely affected HD patients with treatment refractory chorea in an advanced stage of the disease. Primary endpoint of the study was improvement in chorea. Additionally, we evaluated the effects of GPi DBS on the motor part of the Unified Huntington's Disease Rating Scale (UHDRS), bradykinesia, dystonia, functional impairment, psychiatric and cognitive symptoms. Side effects were systematically assessed. Results: The chorea subscore was significantly reduced postoperatively (−47% six months, −40% twelve months postoperatively). The UHDRS total motor score was significantly reduced at six months postoperatively (- 17%) but the effect was not sustained twelve months after the operation (- 5%). Pallidal DBS did not improve other motor symptoms or functional impairment. There was no effect on psychiatric symptoms or cognition. A number of side effects were noted, especially spasticity in three of the patients. Conclusions: Pallidal DBS is a treatment option for HD patients with severe pharmacologically refractory chorea. Further studies are needed to define optimal candidates for this procedure. Highlights: DBS of the GPi significantly improves chorea in advanced stage Huntington's disease patients. DBS also improves the Unified Huntington's disease total motor score. The risk of side effects of the operation may be increased in the advanced stage of the disease.